Representasi Dampak Krisis Lingkungan dalam Puisi-Puisi Karya Taufiq Ismail: Kajian Ekokritik Greg Garrard - Nurul Hidayah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Environmental damage caused by human activities has become an increasingly pressing global issue. Poetry as a literary work has the power to represent ecological problems symbolically and critically. This study aims to describe the representation of the impact of the environmental crisis in Taufiq Ismail's poems, namely "Menengajah Ke Atas, Merenungi Ozone yang Tak terlihat" and "Membaca Tanda-Tanda." The analysis is based on Greg Garrard's ecocritical study. This study uses a qualitative method with content analysis techniques. There are two stages of analysis, namely the literal and symbolic meaning of the poems, then an ecocritical interpretation is carried out based on Garrard's categories which include pollution, wilderness, apocalypse, dwelling, animals, and earth. The results of the study indicate that both poems represent the impact of the environmental crisis through health problems due to pollution and radiation, damage to water and forest ecosystems, climate change, threats to human living space, and the decline in biodiversity. The research findings also show that the most dominant categories are pollution and apocalypse, which confirms that the environmental crisis in Taufiq Ismail's poems is the result of human behavior that ignores nature. Thus, Taufiq Ismail's poems not only function as aesthetic works, but also as cultural criticism and moral warnings for humanity.